2021
DOI: 10.3389/fpsyg.2021.721670
|View full text |Cite
|
Sign up to set email alerts
|

Translation and Validation of the Short Form of the Fear of Dental Pain Questionnaire in China

Abstract: The short form of the Fear of Dental Pain Questionnaire (s-FDPQ) is a validated measure developed to screen patients for their fear of pain associated with dental procedures. As there is a high prevalence of dental fear/anxiety in Chinese adults, the primary aim of our study was to translate the s-FDPQ into standard Mandarin and explore its reliability and validity with Chinese adults. The second aim of our study was to explore fear of dental pain (FDP) scores in relation to dental attendance, anxiety and gend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
(39 reference statements)
0
2
0
Order By: Relevance
“…Between 1971 and 2015, a systematic, retrospective study revealed that ~10% of children and adolescents suffer from dental anxiety ( 3 ). However, other studies have suggested that the rate may be significantly higher ( 4 , 5 ), and survey data in several regions of China indicate that CDA prevalence may be as high as 50% ( 6 8 ). Rather than easing CDA, modern behavior management techniques focus on ensuring children are obedient.…”
Section: Introductionmentioning
confidence: 94%
“…Between 1971 and 2015, a systematic, retrospective study revealed that ~10% of children and adolescents suffer from dental anxiety ( 3 ). However, other studies have suggested that the rate may be significantly higher ( 4 , 5 ), and survey data in several regions of China indicate that CDA prevalence may be as high as 50% ( 6 8 ). Rather than easing CDA, modern behavior management techniques focus on ensuring children are obedient.…”
Section: Introductionmentioning
confidence: 94%
“…According to the International Association for the Study of Pain “Pain is an unpleasant sensory and emotional experience associated with defined or potential tissue damage or described in respect to such damage” [ 1 ]. The fear of dental procedures and treatments is one of the strongest fears in both paediatric and adult age groups [ 2 , 3 , 4 ]. This is particularly related to dental procedures in which needles are used, such as in local anaesthesia [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%